PREPONDERANT MODALITY IN STUDENTS’ ENGAGING ARGUMENTATIVE ESSAYS - Marwito Wihadi; Eva Tuckyta Sari Sujatna (English Review: Journal of English Education, 2019)
Expressing modality in Appraisal is cordially expected to be prevalent in argumentative writings in that writers in the Engagement System set up negotiation or alternative points of views. Three conveniently selected student-writers’ hortatory argumentative essays in English in which they were course-instructed in an accredited language institution were linguistically analyzed as to pinpoint their aptness to employ particular modality, furthermore to discuss the feasible resource factors on their employment. It was found out that they were prone to be lack of commitment as they delivered their stances, therefore attempting the readers to be engaged in an argumentative discourse to construe the meanings. Subsequently, they had difficulty in manipulating epistemic and deontic modality, owning mundane syntactic constructions and imparting limited device ranges. Therefore, applicably explicit genre-based instructions are in the need, bearing in mind the factual functions of modality in arguability of the utterances as well the resourceful linguistic features of modality.